2012
DOI: 10.1073/pnas.1116058109
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic immunological synapses do not restrict the action of interferon-γ to antigenic target cells

Abstract: Following antigen recognition on target cells, effector T cells establish immunological synapses and secrete cytokines. It is thought that T cells secrete cytokines in one of two modes: either synaptically (i.e., toward antigenic target cells) or multidirectionally, affecting a wider population of cells. This paradigm predicts that synaptically secreted cytokines such as IFN-γ will preferentially signal to antigenic target cells contacted by the T cell through an immunological synapse. Despite its physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 20 publications
3
47
1
Order By: Relevance
“…Two scenarios have been proposed: (1) CD8 + T cells become indiscriminate killers and eliminate ALV by direct cell-cell engagement, or (2) CD8 + T cells target sensitized stromal cells resulting in indirect, bystander killing of ALV. Interestingly, it was recently demonstrated that IFNγ not only acts synaptically (i.e., toward antigenic target cells) but multidirectionally affecting non-antigenic bystanders in vitro 55 . Obviously, the kinetics of elimination in these 2 scenarios would be very different.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two scenarios have been proposed: (1) CD8 + T cells become indiscriminate killers and eliminate ALV by direct cell-cell engagement, or (2) CD8 + T cells target sensitized stromal cells resulting in indirect, bystander killing of ALV. Interestingly, it was recently demonstrated that IFNγ not only acts synaptically (i.e., toward antigenic target cells) but multidirectionally affecting non-antigenic bystanders in vitro 55 . Obviously, the kinetics of elimination in these 2 scenarios would be very different.…”
Section: Resultsmentioning
confidence: 99%
“…While perforin, not needed in our model (Fig. 3H), depends on effector-target conjugates for achieving cell death, IFNγ- and TNFα-dependent killing can be mediated without direct target contact, 60 and can act multidirectionally affecting non-antigenic bystanders 55 . Since ALV were eliminated in sensitized stroma of K b /SIY tumors but not in L d -tumors, we propose that stromal cross-presentation, T cell-stromal engagements, and subsequent high cytokine release in this model are helping the elimination of ALV and prevention of re-growth of cancer variants.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of cytokine-mediated communication, however, indicate that soluble proteins escape the T cell-target cell interface very quickly (Feinerman et al, 2010; Muller et al, 2012; Sanderson et al, 2012). An alternative strategy for boosting selectivity and efficiency would involve locally increasing the specific activity of secreted molecules.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, TNF-␣ has been reported to be secreted multidirectionally following the ligation of CD8 ϩ T cells, suggesting that it might act on bystander cells in addition to cognate targets (25). IFN-␥ secretion has generally been assumed to be synaptic and highly localized, though multidirectional secretion has also been reported (25)(26)(27). In a recent study, IFN-␥ produced by CD4 ϩ T cells was able to induce bystander killing of Leishmania major parasites in the skin (28).…”
Section: Discussionmentioning
confidence: 99%